“The wound, the sore, the search for healing”: notes on sexual violence situations against women in therapeutic communities (Emancipação, 2024)
This article seeks to address sexual violence against women in Therapeutic Communities (TCs) as a violation of human rights. This is a descriptive and exploratory study, through qualitative documentary research, through inspection reports from TCs and reports in media outlets about cases of sexual violence in institutions, addressing the links between gender, mental health and sexual abuse, under the analytical tool of intersectionality. The results indicate that sexual violence appears in a dispersed manner in reports, as opposed to reports in the media. Despite rights violations, TCs receive increasing state subsidies, marking the State's collusion with institutions that perpetuate violence against women and the violation of their rights – sexual and reproductive, health, freedom, free religious expression. It is necessary to address the phenomenon of sexual violence in TCs, to perpetuate the invisibility of the topic.
Keywords: Gender; Mental health; Sexual abuse